2015
DOI: 10.1111/irel.12091
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Wage Channels of Adjustment

Abstract: The effects of minimum wage increases in [2007][2008][2009] are analyzed using a sample of restaurants from Georgia/Alabama. Store-level payroll records provide precise measures of compliance costs. Examined are multiple adjustment channels. Exploiting variation in compliance costs across restaurants, we find employment and hours responses to be variable and in most cases statistically insignificant. Channels of adjustment to wage increases and to changes in non-labor costs include prices, profits, wage compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 49 publications
4
62
0
2
Order By: Relevance
“…Previous studies [35][36][37][38][39][40] have indicated that although aggregate employment may not decrease in response to MW increases, employers do respond to labor cost increases by adopting one or more offsetting actions through recognized channels of adjustment [3]. Businesses can make two types of strategic adjustments to stay competitive in the face of a shock such as wage increases: quality enhancement or cost minimization [44,45].…”
Section: Impact Of Minimum Wage Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [35][36][37][38][39][40] have indicated that although aggregate employment may not decrease in response to MW increases, employers do respond to labor cost increases by adopting one or more offsetting actions through recognized channels of adjustment [3]. Businesses can make two types of strategic adjustments to stay competitive in the face of a shock such as wage increases: quality enhancement or cost minimization [44,45].…”
Section: Impact Of Minimum Wage Changesmentioning
confidence: 99%
“…Quality enhancement strategies focus on increasing product quality in some way, leading to the ability to raise prices [45]. Cost-minimization adjustments reduce overall labor costs by changing wage policies, such as reducing normal wage increases; cutting "nonwage compensation" such as free or discounted meals, on-the-job training, or paid breaks; greater use of part-timers; limiting the availability of overtime hours; increased performance standards; cross-training employees for multitasking; and getting more work from each employee [3,37,45]. Additional cost minimizing adjustments focus on other aspects of the business, such as reducing waste, water, and electricity use [3].…”
Section: Impact Of Minimum Wage Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…MDU poveikis gali būti tiriamas tiek mikro, tiek makro lygmeniu. Prisitaikymą prie kintančio MDU aprašo koregavimo kanalų teorija (Hirsch, 2015). Koregavimo kanalai gali būti nustatomi pagal konkurencinio, institucinio-elgsenos, ar monopsoninio modelio prielaidas.…”
unclassified
“…Atsižvelgiant į tai, lyginamiesiems MDU reguliavimo poveikio tyrimams yra tikslinga taikyti daugiamatės statistiko metodus. Dauginė atitikties analizė (Abdi, 2007;Husson, 2010) leidžia susieti kokybinius rodiklius nenurodant konkretaus priežastinio ryšio. Taigi straipsnyje nagrinėjama ši mokslinė problema: kokios yra MDU ir makroekonominių rodiklių sąsajos Europos Sąjungos (ES) valstybėse narėse ir kaip galima tobulinti MDU reguliavimą?…”
unclassified